Menopause Health Education and Dhikr Techniques for Managing Menopausal Anxiety at 'Aisyiyah Member in Wonosari, Bondowoso - Rozifa, Annisa' Wigati; Qodliyah, Awwalul Wiladatil (Indonesian Journal of Community Services, 2025)
Hormonal fluctuations during menopause often cause physical and psychological changes, including increased anxiety. A lack of understanding about menopause and strategies for managing anxiety can negatively impact women's well-being. This community service program aims to increase women's knowledge about menopause and introduce dhikr (remembrance of God) as a spiritual method for managing anxiety. Participants were 43 women from the Wonosari of 'Aisyiyah, Bondowoso. They were purposively selected active women in the perimenopausal to menopausal age range. Recruitment was conducted through coordination with 'Aisyiyah administrators and those willing to participate in this activity. The intervention program consisted of a menopausal health education session covering hormonal changes, physical and emotional symptoms, health risks, and coping strategies through interactive lectures and Q&A sessions, accompanied by visual presentations to facilitate understanding. Next, participants engaged in a guided dhikr practice session that covered breathing techniques and the repetition of dhikr phrases. We used pretests and posttests to assess increases in participants' knowledge and changes in their anxiety levels. Results showed a significant increase in knowledge, with the number of participants in the good knowledge category increasing from 16 to 35. The dhikr intervention was also effective in reducing anxiety, as evidenced by the increase in participants with no anxiety from 10 to 22 and the disappearance of the severe anxiety category. These findings confirm that the combination of menopausal health education and dhikr practice can be an effective and applicable strategy to help women navigate hormonal changes more adaptively and confidently. This program has the potential to be replicated in other communities to improve the well-being of menopausal women more broadly.